The mayinje house : an architecture of activism - Ferrari, Jonathan E (School of Architecture, Planning and Geomatics, 2023)
My initial interest in undertaking a research project in Cape Town, was locked by my outsider's gaze into vibrant urban images of townships and informal settlements. It was nurtured by a free South Africa's much publicized need for decent housing, and my projection of involvement with design efforts to develop viable housing options for the great number of beautiful people living in lovely, crowded, fire-prone shack communities. I had been nurturing a conviction for the possibility of utilizing waste-stream resources -'trash'- in an evocative, ecological production of architecture - an interest spawned through the concept of industrial ecology, and my background in the biological sciences. A coinciding potential seemed ripe. It has been said that necessity is the mother of invention. Nowhere is this perhaps truer than in South Africa. The informal settlements of South Africa are a marvel of ingenuity and creativity where the processes of invention are continually fuelled by necessity's perpetual dance through the mazes of adversity; mazes, which are strewn with the fallout of a consumer society - created and driven by market forces. One of the most prevalent creations of the township is the 'shack.' In a condition where neither the state nor the private sector can provide appropriate housing in sufficient quantity, these dwellings are the people's solution to the immediate need for shelter. Many of the material resources used in the construction of shacks come from the waste stream of the country's consumer market. Formally, and materially shacks bear little resemblance to traditional South African dwellings. The two types are similar however, in that their material value exists primarily through their social and individual uti.lity and their location. A traditional dwelling has little economic value as a commodity ty because it is constructed with free building materials available in the natural environment. 1 The shack's use of free waste materials and relatively inexpensive used materials similarly confounds the capitalist system's commodification of the dwelling. Ironically, a dwelling with little to no market value can restrict entry into a capitalist society. Home ownership is one of the passes required in order to access credit - which is needed to become a 'cardholding' member of the consumer society, with all its benefits and demands. 2 There are however, numerous examples from the informal settlements and townships where goods of significant economic value are created from free resources. Folk artwork and craftwork from South African Townships is recognized all over the world and has significant market value. Scale replicas of Harley Davidsons are made from scrap wire and oil tins, plastic sheeting, and plastic bags. Telephone wire is used as a substitute for reeds to weave intricate baskets in